Formułowanie subiektywnych rozkładów a priori - podejście parametryczne i nieparametryczne - Biskup, Dariusz (Subjective prior elicitation - parametric and non-parametric approach, 2008)
Prior distribution elicitation is the basic requirement of the Bayesian statistical inference. If there is prior knowledge about a particular problem, then it is necessary to „translate” it into the form of probabilistic distribution. The paper describes the most important ways of prior elicitation basing on the expert’s knowledge. The parametric approach was presented, in which it is assumed that the prior distribution can be described using some predetermined class of distributions. The non-parametric approach in turn does not assume any restrictions on the form of the prior. The topic of group prior elicitation was also mentioned.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (20); 2008; nr 1195, s. 71-80